Carbon emissions in China's urban residential building sector through 2060: A dynamic scenario simulation. (1st September 2022) - Huo, Tengfei; Ma, Yuling; Xu, Linbo; Feng, Wei; Cai, Weiguang
Abstract: Carbon-reduction effect of the urban residential building sector is crucial to the carbon neutrality target. This study aims to explore the interaction mechanism among influencing factors and simulate the future evolutionary trajectories of urban residential building carbon emissions (URBCE). An integrated dynamic emission assessment (IDEA) model is innovatively established by coupling the system dynamics (SD) model and a bottom-up end-use decomposition model. Combining with the scenario analysis approach, this IDEA model is applied in China's urban residential building sector from 2000 to 2060. Results show that under the baseline scenario, the URBCE will fail to peak before 2030 but will peak at 1.19 Bt CO2 in 2037. In comparison, it will peak at 0.79 Bt CO2 in 2025 and decline to 0.17 Bt CO2 in 2060 under carbon-neutral scenario, which can be neutralized by negative carbon technologies. Different end-uses and climate zones show marked discrepancies in emission-reduction potential, with the contribution of heating and appliances being over 50%. Sensitivity analyses shows that the low-carbon awareness, electrification rate, proportion of clean energy generation and technological progress contribute positively to the early peak of URBCE. This study provides a deeper understanding of China's potential peaking paths and can assist policy-makers in better evaluating emission paths for other nations and regions. Graphical abstract: Image 1 Highlights: Develops an IDEA model by combining system dynamics model and LEAP model. Explores the interaction and feedback mechanism among different levels of factors. Simulates the URBCE by combining the IDEA model and scenario analysis approach. Urban residential buildings will peak at 1.19 Bt CO2 in 2037 under the BAU scenario. Different end-uses and climate zones show marked discrepancies in emission-reduction potential.